1987
DOI: 10.3109/00365528708991878
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids and the Irritable Bowel Syndrome: The Effect of Wheat Bran

Abstract: Short-chain fatty acids (SCFA) in faeces were examined in 18 patients with the irritable bowel syndrome (IBS) during treatment with wheat bran or placebo. In the placebo period, the patients could be classified in accordance with the faecal concentrations of SCFA into one group with low concentrations (mean, 40 mmol/l; range, 19-77 mmol/l; 10 patients) and another with high concentrations (mean, 168 mmol/l; range, 145-187 mmol/l; 8 patients). The concentrations of SCFA differed (P less than 0.001) in both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 16 publications
3
48
1
2
Order By: Relevance
“…This prompted us to measure fermentation products in the rectum. Alterations in fecal SCFA concentrations have indeed been described previously in patients with IBS [28][29][30]. However, we did not find any significant differences in rectal SCFA levels in our study, which notably were measured after complete rectal emptying.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This prompted us to measure fermentation products in the rectum. Alterations in fecal SCFA concentrations have indeed been described previously in patients with IBS [28][29][30]. However, we did not find any significant differences in rectal SCFA levels in our study, which notably were measured after complete rectal emptying.…”
Section: Discussioncontrasting
confidence: 64%
“…Dialysis bags were stored overnight at +4 C and bathed in 08. 30 Rheomacrodex solution; there was no need for additional lubrication upon insertion. The dialysis bags were left for 4 h to obtain equilibrium with rectal luminal fluid [11], and dialysate was thereafter aspirated from the bags using a syringe and needle, transferred into plastic vials and stored at -80 C until analysis.…”
Section: Rectal Equilibrium Dialysismentioning
confidence: 99%
“…Patients with IBS apparently have continuously abnormal concentrations of SCFAs in feces, either high or low. IBS patients with low levels of SCFAs have lower mean stool mass and longer transit times than those with high concentrations of SCFAs in feces [23]. The relative contribution of luminal SCFAs to the pathogenesis of IBS still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown an increase in short chain fatty acids (SCFA) concentration in at least a subset of IBS stool samples. [16][17][18] Butyrate and acetate are common SCFAs produced by commensal bacteria in the human gut and are necessary for normal functioning of host-microbiota interactions. 19 The described IBS-related microbiota, (Ruminococccaceae and Clostridium cluster XIVa) are known to be enriched in producers of SCFAs.…”
Section: Extraneous Confounders: Diet and Lifestylementioning
confidence: 99%